Shifting of Nonlinear Phenomenon in the Boost converter Using Aquila Optimizer - Belkacem Korich; Derradji Bakria; Djamal Gozim; Redha Djamel Mohammedi; Mohamed Elbar; Ali Teta (The Journal of Engineering and Exact Sciences)
Power electronics circuits are characterized by nonlinear dynamics, because of the cyclic switching between a finite number of topologies, which can give rise to a variety of behaviors. DC/DC converters are prone to nonlinear phenomena, such as bifurcations, quasi-periodic and chaotic responses, which can make it difficult or even impossible to analyze, predict, and control the converter's behavior. This paper offers an examination of the chaotic behavior of the DC/DC boost converter and suggests an optimized PID controller as solution to the nonlinear phenomena. Aquila optimizer AO is employed to determine the ideal parameters for the controller by computing the discrepancy between the reference current and the value of the inductor current, as well as the discrepancy between the inductor current readings during switch openings. The simulation results using MATLAB demonstrate the effectiveness of the proposed solution.